2010
DOI: 10.33899/rden.2010.9019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Rugae Pattern Between Dentate and Edentulous Patients in Iraqi Sample

Abstract: Aim:To explore the volatile topographic changes occurring in the palatal rugae after aging and loss of all teeth. Materials and methods: The total sample consists of 40 Iraqi participants in 2 , dentate and edentulous , groups. Their maxillary casts were minutely observed. Number, lengths, qualitative characteristics, and medial position of the rugae ends were recorded. Results: Many differences were observed between the 2 groups. Conclusions: Palatal rugae were topographically changed greatly after aging and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
2
6
1
1
Order By: Relevance
“…[8] When palatal rugae have anomalies and abnormalities, there are considered as reflection of abnormal growth those could be the source of forensic identification. [1] Concerning the gender, in this study, the total number of rugae was slightly fewer in females than in males, but statically not significant, this result agrees with Saraf et al, [9] Fahmi et al, [10] and Kapali et al [4] As a shape of rugae, in this study, the total of wavy and curveshaped rugae was the most common representing 70.63% of the total samples of the present study and these results agree with previous studies done by Venegas et al [11] and Indira et al [12] The most common type is the wavy shaped and this result agrees with Jawad [13] and disagrees with Indira et al [12] that they found the most common is the curve, and this may be due to the different regional or race samples.…”
Section: Discussionsupporting
confidence: 92%
“…[8] When palatal rugae have anomalies and abnormalities, there are considered as reflection of abnormal growth those could be the source of forensic identification. [1] Concerning the gender, in this study, the total number of rugae was slightly fewer in females than in males, but statically not significant, this result agrees with Saraf et al, [9] Fahmi et al, [10] and Kapali et al [4] As a shape of rugae, in this study, the total of wavy and curveshaped rugae was the most common representing 70.63% of the total samples of the present study and these results agree with previous studies done by Venegas et al [11] and Indira et al [12] The most common type is the wavy shaped and this result agrees with Jawad [13] and disagrees with Indira et al [12] that they found the most common is the curve, and this may be due to the different regional or race samples.…”
Section: Discussionsupporting
confidence: 92%
“…This identification of rugae depends on several factors such as presence or absence of tooth, palatal height changes caused by degenerating alveolar bone after tooth loss, poorly delineated rugae eminences, indistinct outline or form of alveolar arches, and more complex patterns (line, curve, circle, bifurcated, sinnous) or non-complex patterns (line only) in some cases [14] . In the present study significant differences were observed between the mean values of both the groups and also on the distribution of the rugae pattern between both the groups similar to studies by Jawad IA [8] , Kapali et al [15] , Bhatt.G [16] . Among completely edentulous individuals (group A) Sinnous pattern (2.1±1.65) is more common followed by line (1.4 ± 1.39); curve (1.4 ± 1.48) and bifurcated type (0.6 ± 0.81) whereas in partially edentulous individuals (group B) Line pattern (2.6 ± 1.71) is more common followed by sinnous (2.2 ± 1.74); circle (0.6 ± 0.78) and bifurcated type (0.3 ± 0.61) based on number and distribution.…”
Section: Discussionsupporting
confidence: 91%
“…Rugae pattern, well protected by lips, cheek, tongue, buccal pad of fat and teeth in certain conditions such as burnt bodies in incident of fire or higher temperatures or where bodies have decomposed severely and encountered high impact trauma can be an effective personal identification tool [7] . Preservation of rugae plays an important role in prosthetic rehabilitation especially among completely edentulous individuals as it acts as the stress bearing area that prevents displacement of the denture anteriorly [8] , guides in setting the maxillary teeth at the anterior region and provides indirect retention in denture extension cases [9] . Nevertheless rugae pattern are least susceptible to external environment changes and are unique to every individual often considered as a consistent relevant marker of forensic importance [10] .…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 8 9 11 13 19 20 21 22 ] In spite of these advantages of rugoscopy, the scale of reliability on this technique is unclear, with some studies contradicting their utility in forensic medicine. [ 15 16 18 23 24 25 26 ] Moreover availability of ante mortem casts or any records like photographs is must for identification using palatoscopy.…”
Section: Discussionmentioning
confidence: 99%